Reactive capture using metal looping: the effect of oxygen. (4th May 2021) - Dowson, George R. M.; Cooper, Joshua; Styring, Peter
Abstract : By looping magnesium via electrolysis, capture and conversion of CO2 to higher-value products can happen simultaneously. The effect of other gases on this process, particularly oxygen, in waste CO2 streams is investigated and shown not to cause adverse effects. Abstract : In the effort to create a sustainable future economy, the ability to directly convert dilute gas-phase CO2 in waste gas streams into useful products would be a valuable tool, which may be achievable using Grignard reagents as both the capture and the conversion materials. The magnesium salt by-product can be recovered, and metallic magnesium regenerated through conventional high-efficiency electrolysis. This stoichiometric approach is known as metal looping, where the magnesium acts as the energy vector for the capture and conversion, allowing both to occur at room temperature and atmospheric pressure. However, the process has only previously been demonstrated with 12% CO2 in nitrogen mixtures. If we consider this process in a real post-combustion flue gas conversion scenario, the sensitivity of Grignard reagents to other gases (and water vapour) must be considered. While some of these gases and the water vapour are relatively easily removed, in most flue gas streams the most common other gas present, oxygen, would be far more challenging to excise, and oxygen is known to react with Grignard reagents, albeit slowly. In order to determine if higher oxygen concentrations could be tolerated, allowing the possibility of a variety of relatively inexpensive and possibly profitable direct CO2 conversion pathways to be developed, a range of industrially relevant CO2 /O2 mixtures were made and carefully bubbled through phenylmagnesium bromide solutions.